THE DIFFERENTIATED CHARACTERISTICS OF GIRLS' PSYCHOLOGICAL AND PEDAGOGICAL PECULIARITIES ACCORDING TO THE DEGREE OF THEIR SOCIAL AND PEDAGOGICAL NEGLECT - Іванна Парфонович (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
Theoretical approaches to the explanation of the nature and characteristics of girls' deviant behavior display are analyzed. The peculiarities of psychological and pedagogical characteristics of girls of different degrees of social and pedagogical neglect are established, based on the definitions of «troubled child», «social disorganization and exclusion», «social abandonment», «pedagogical neglect», «social and pedagogical neglect», «individuals of risk groups «individuals of deviant behavior» and their hierarchy. The application of social and pedagogical methods and forms of work with girls, which are socially, pedagogically, and socio-pedagogically neglected, are examined through the appliance of differentiated approach. Preventive and organizational measures in social-pedagogical  work with girls, which are socially, pedagogically, and socio-pedagogically neglected, are determined considering the peculiarities of personal development deformation at the stage of «being a troubled child», social disorganization and exclusion.